1997
DOI: 10.1074/jbc.272.11.7431
|View full text |Cite
|
Sign up to set email alerts
|

All-D-Enantiomers of β-Amyloid Exhibit Similar Biological Properties to All-L-β-Amyloids

Abstract: The amyloidogenic peptide ␤-amyloid has previously been shown to bind to neurons in the form of fibrillar clusters on the cell surface, which induces neurodegeneration and activates a program of cell death characteristic of apoptosis. To further investigate the mechanism of A␤ neurotoxicity, we synthesized the all-D-and all-Lstereoisomers of the neurotoxic truncated form of A␤ (A␤ [25][26][27][28][29][30][31][32][33][34][35] ) and the full-length peptide (A␤ 1-42 ) and compared their physical and biological pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
72
0
3

Year Published

1997
1997
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(79 citation statements)
references
References 59 publications
4
72
0
3
Order By: Relevance
“…We suggest an important significance of this finding because a correlation appears to exist between biological effects of A␤ and its aggregation state (7)(8)(9)(10). Furthermore, it is believed that the fibrillar peptide itself represents the neurotoxic species.…”
Section: Ganglioside-containing Vesicles Promote A␤ Fibril Formation mentioning
confidence: 68%
“…We suggest an important significance of this finding because a correlation appears to exist between biological effects of A␤ and its aggregation state (7)(8)(9)(10). Furthermore, it is believed that the fibrillar peptide itself represents the neurotoxic species.…”
Section: Ganglioside-containing Vesicles Promote A␤ Fibril Formation mentioning
confidence: 68%
“…Additionally, both the L-and D-enantiomers of A␤ exhibited nearly identical structural characteristics and induced similar levels of toxicity, implying that A␤ neurotoxicity was mediated by A␤ fibril features instead of any stereoisomer-specific interactions (79). Compounds such as Congo Red, rifampicin, and recognition peptides that bind to and/or inhibit the formation of amyloid fibrils have also been shown to attenuate the toxicity of A␤, further establishing the causal link between A␤ structure and function (21-24, 64, 80, 81).…”
Section: Discussionmentioning
confidence: 98%
“…Disruption of Membrane Lipid Integrity-A␤ peptides interact with membrane lipids such as phosphoinositides (51), phosphatidylglycerol (52), phosphatidylcholine (53), and gangliosides (54). A direct interaction of A␤ with cell membranes was initially proposed by Cotman and co-workers (55), who showed that D-and L-stereoisomers of a truncated form of A␤ induced similar toxicity levels in cultured hippocampal neurons, suggesting that A␤ toxicity does not involve a specific ligand-receptor interaction. Fluorescence spectroscopy measurements indicate that A␤ interaction with the synaptic plasma membrane causes substantial changes in the membrane fluidity both in the bulk lipid milieu and in proximity to integral membrane proteins.…”
Section: Actions Of A␤ On Endogenous Plasmalemmal Ion Channels-mentioning
confidence: 93%